2006
DOI: 10.1007/s10152-006-0036-5
|View full text |Cite
|
Sign up to set email alerts
|

Cirripedia of Madeira

Abstract: We give a list of Cirripedia from Madeira Island and nearby deep water, based on specimens in the collection of the Museu Municipal do Funchal (Histo´ria Natural) (MMF), records mentioned in the literature, and recent collections. Tesseropora atlantica Newman and Ross, 1976 is recorded from Madeira for the first time. The Megabalanus of Madeira is M. azoricus. There are 20 genera containing 27 species, of which 22 occur in depths less than 200 m. Of these shallow water species, eight are wide-ranging oceanic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 25 publications
(18 reference statements)
0
36
0
1
Order By: Relevance
“…Blue whale, Balaenoptera musculus (Linnaeus, 1758) Southern hemisphere South Atlantic Nilsson-Cantell, 1939b Fin whale, Balaenoptera physalus (Linnaeus, 1758) North-east Atlantic, Madeira Wirtz et al, 2006 Sperm whale, Physeter catodon Linnaeus, 1758 Southern hemisphere Hiro, 1935 Northern bottlenose whale, Hyperoodon ampullatus (Flower, 1882) Blue whale, Balaenoptera musculus (Linnaeus, 1758) Southern hemisphere South Atlantic Nilsson-Cantell, 1939b Fin whale, Balaenoptera physalus (Linnaeus, 1758) North-east Atlantic, Madeira Wirtz et al, 2006 Sperm whale, Physeter catodon Linnaeus, 1758 Southern hemisphere Hiro, 1935 Northern bottlenose whale, Hyperoodon ampullatus (Flower, 1882)…”
Section: Introductionmentioning
confidence: 99%
“…Blue whale, Balaenoptera musculus (Linnaeus, 1758) Southern hemisphere South Atlantic Nilsson-Cantell, 1939b Fin whale, Balaenoptera physalus (Linnaeus, 1758) North-east Atlantic, Madeira Wirtz et al, 2006 Sperm whale, Physeter catodon Linnaeus, 1758 Southern hemisphere Hiro, 1935 Northern bottlenose whale, Hyperoodon ampullatus (Flower, 1882) Blue whale, Balaenoptera musculus (Linnaeus, 1758) Southern hemisphere South Atlantic Nilsson-Cantell, 1939b Fin whale, Balaenoptera physalus (Linnaeus, 1758) North-east Atlantic, Madeira Wirtz et al, 2006 Sperm whale, Physeter catodon Linnaeus, 1758 Southern hemisphere Hiro, 1935 Northern bottlenose whale, Hyperoodon ampullatus (Flower, 1882)…”
Section: Introductionmentioning
confidence: 99%
“…Megabalanus azoricus is an insular Atlantic species inhabiting shallow subtidal bedrock of St. Helena Island, the Azores, Madeira and the Canaries Archipelagos (Wirtz et al, 2006). This species is the largest and the third most common shallow-water barnacle of the Azores.…”
Section: Introductionmentioning
confidence: 99%
“…Ross (1969) and Amaral et al (2010) mentioned Newmanella radiata as an encrusting component common on hulls of wrecked ships. Balanus trigonus has been observed in greater depths (Wirtz et al 2006) and occupies a variety of biogenic and abiogenic substrata (Farrapeira 2010), including artificial reefs in New Zealand (Russell 1975) and Florida (Nelson et al 1994), and shipwrecks between 20 and 30 m deep (Wendt et al 1989, Ponti et al 2002, Amaral et al 2010 Megabalanus tintinnabulum has been reported up to 38 m deep on offshore oil platforms (Lewbel et al 1987, Yan et al 2006, and on a shipwreck that lay in 27 m of water (Walker et al 2007).…”
Section: Discussionmentioning
confidence: 99%